2006
DOI: 10.1063/1.2335685
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the surface and structural quality of N-face InN grown by molecular beam epitaxy

Abstract: The authors demonstrate the impact of growth kinetics on the surface and structural properties of N-face InN grown by molecular beam epitaxy. Superior surface morphology with step-flow growth features is achieved consistently under In-rich conditions in a low-temperature region of 500–540°C. Remarkably, off-axis x-ray rocking curve (ω scans) widths are found to be independent of the growth conditions. The band gap determined from optical absorption measurements of optimized InN is 0.651eV, while photoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
85
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 27 publications
(25 reference statements)
3
85
1
Order By: Relevance
“…There is no discernable difference between the In-and N-face InN samples, as expected for the improved crystalline quality and concomitant low background electron density and high mobility for both polarities. 9,16 Liu et al 13 have shown a similar dependence on carrier concentration for the terahertz radiation from InAs.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…There is no discernable difference between the In-and N-face InN samples, as expected for the improved crystalline quality and concomitant low background electron density and high mobility for both polarities. 9,16 Liu et al 13 have shown a similar dependence on carrier concentration for the terahertz radiation from InAs.…”
mentioning
confidence: 63%
“…Terahertz radiation from In-͑Ref. 9͒ and N-face 16 n-InN samples with a bulk carrier concentration n bulk ranging from 10 17 to 10 19 cm −3 is examined and shows a significant decrease as n bulk increases. These results are consistent with the dominant mechanism for terahertz generation in InN and InAs being the current associated with the diffusion of the photogenerated electrons at elevated electron temperature ͑photo-Dember effect͒ and the redistribution of the background electrons under drift.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the highest-quality InN epitaxial thin films have been obtained by rf-plasma-assisted molecular-beam epitaxy (rf-MBE). 16 However, with regard to SAG by MBE, a E-mail: kamimura@katsumi.ee.sophia.ac.jp (J. Kamimura), kishino@katsumi.ee.sophia.ac.jp (K. Kishino). it is difficult to achieve selectivity owing to the lack of gas phase reactions and the high sticking coefficient of group III materials on dielectric masks.…”
Section: Mev At 4 K Copyright 2011 Author(s) This Article Is Distrimentioning
confidence: 99%
“…Bulk material is not available, but high quality films on sapphire ͑either directly or using various buffer layers͒ have been fabricated by molecular beam epitaxy ͑MBE͒ [1][2][3][4] and also by metal-organic chemical vapor deposition ͑MOCVD͒. 5,6 The properties of the material are greatly affected by the layer thickness and substrate material, as well as the growth temperature and stoichiometry.…”
mentioning
confidence: 99%